Appraisal and Collaboration for Teachers’ training: beyond the common sense’s oxymoron - Di Stasio, Margherita (Formazione & insegnamento, 2017)
In this contribution we will try to read the appraisal as a support in reflective teachers’ training path; in a school and community dimensions, we will consider it as incentive to sharing practices for peer review process oriented to teachers professional development and school improvement. We will conduct this analysis form an historical perspective from the Autonomy to the Buona Scuola.